Technology, Excretion and the Good Life - Biswas, Tanushree (European Journal of Sustainable Development, 2014)
This paper discusses an ontological crisis that emerges from the modern life which is inherently related to modern technology, with insights from Heidegger's ontology of technology and my observations in Ladakh. There are two central underlying assumptions in my approach: ? “Technological” progress lies at the heart of earning the identity of being a developed country. ? The way we relate to objects of knowledge, determines the nature of knowledge. Heidegger shows that what qualifies as science and technology for the minority world today, has not always been the way it was conceived. The validity and truth of modern knowledge is held under profound suspicion because only that which can be measured, calculated, stored, called-upon and challenged to deliver comes into being in this worldview. This tendency pervades every aspect of our lifestyles including mundane acts such as excretion. It is through such mundane acts, that relations with existence as a whole are formed and maintained and progressive knowledge is possible; knowledge which makes sustainability and the good life possible. Key Word: Technology, Excretion, Ladakhi, Heidegger's Ontology of Technology.